How I Grow: Months Eleven and Twelve - Millie Ferrer; Anne M. Fugate (EDIS)
During these months, your adventurous baby needs you to provide a safe place to explore. Having the freedom to explore, plus your encouragement, will help your baby learn. Your baby also needs reasonable limits. Reasonable limits keep your baby safe and begin to teach him necessary boundaries. In addition to keeping him safe, boundaries also help him learn how to interact with others. By providing both the freedom to explore and safe, reasonable limits, you will help your baby develop physically, socially, emotionally, and intellectually. This document is FCS2222, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, University of Florida, IFAS, Gainesville FL 32611. First published: August 2003.